Association between type 2 diabetes mellitus and disability: What is the contribution of diabetes risk factors and diabetes complications?: 2型糖尿病与残疾之间的关系:糖尿病危险因素与糖尿病并发症可造成什么影响?. Issue 9 (6th April 2018) - Tabesh, Maryam; Shaw, Jonathan E.; Zimmet, Paul Z.; Söderberg, Stefan; Koye, Digsu N.; Kowlessur, Sudhir; Timol, Maryam; Joonas, Noorjehan; Sorefan, Ameena; Gayan, Praneel; Alberti, K. George M.M.; Tuomilehto, Jaakko; et al.
Abstract: Background: The aim of this study was to evaluate the association between type 2 diabetes and disability in Mauritius and to assess the extent to which the effect of diabetes is explained by diabetes risk factors and concomitant complications. Methods: Data from a national survey in the multiethnic nation of Mauritius, which comprises South Asians and African Creoles, were analyzed. Disability was measured using the Katz activities of daily living questionnaire in participants aged >50 years. Results: Among 3692 participants, 487 (13.2%) had some level of disability. Diabetes was associated with significantly higher risk of disability (odds ratio [OR] 1.67; 95% confidence interval [CI] 1.34–2.08). After adjusting for demographic, behavioral, and metabolic factors, as well as comorbidities, disability was significantly associated with diabetes among African Creoles (OR 2.03; 95% CI 1.16–3.56), but not South Asians (OR 1.27; 95% CI 0.98–1.66). Obesity explained much of the association between diabetes and disability (excess percentage of risk: 26.3% in South Asians and 12.1% in African Creoles). Obesity, history of cardiovascular disease (CVD), asthma‐like symptoms, and depression together explained 46.5% and 29.0% of the excess risk in South Asians and African Creoles, respectively. Conclusions: Diabetes is associated with a 67% increased risk of disability. Diabetes risk factors and comorbidities explain more of the association between diabetes and disability among South Asians than Africans. Obesity and history of CVD explained the largest percentage of the relationship between diabetes and disability, indicating that weight and CVD management may be helpful in controlling disability related to diabetes. Abstract : Highlights Diabetes is associated with 67% increased odds of disability. The prevalence of disability is higher among women than men. Forty per cent of the association of diabetes with disability can be explained by risk factors and concomitant disease. Obesity explained the largest percentage of the relationship between diabetes and disability, indicating that weight management may be helpful in controlling disability related to diabetes.